TEKNIK PENERJEMAHAN NASKAH PIDATO KENEGARAAN PRESIDEN REPUBLIK INDONESIA DARI BAHASA INDONESIA KE DALAM BAHASA INGGRIS - Anam Sutopo (Universitas Muhammadiyah Surakarta, 2012)
This study aims at describing the translation technique applied by the translators in the translation text of the state address of the President of the Republic of Indonesia. This study belongs to a qualitatif descriptive research. The research strategy applied in this study is an embedded case study. The data include words, phrases and sentences in the translation of the state address of the President of the Republic of Indonesia in 2006 which are written in Bahasa Indonesia and English (317 data), the translation experts’ statement about the accuracy and the English Native Speakers’ statement related to the acceptability and readibility. The data sources are informants and documents. Informants are the translators of the state address of the President of the Republic of Indonesia in 2006, key informants or translation experts and the English Native Speakers selected with purposive sampling technique. The documents refer to the state address of the President of the Republic of Indonesia in 2006 and its translation and all the statements taken from both translation experts and the English native speakers. The techniques for data collecting are questionnaire, in-depth interview and content analysis. The data validity is source and method triangulation. The collected data are analysed with interactive analysis model. The results of the research show that first, there are 11 techniques of translation applied by the translator. They are amplification technique 64 data (9,37%), pure borrowing technique 63 data (9,22%), natural borrowing technique 43 data (6,30 %) calque technique 67 data (9,81%), description technique 11 data (1,61%), generalization technique 56 data (8,20%), literal technique 263 data (38,51%), modulation technique 35 data (5,12%), reduction technique 4 data (0,59%), transposition technique 58 data (8,49%), and addition technique 19 data (1,61%). Second, The technique of translation applied by the translators is dominated by literal translation.